Numerical Investigations and Analysis of Cu2ZnSnS4 Based Solar Cells by SCAPS-1D - M. Djinkwi Wanda; S. Ouédraogo; F. Tchoffo; F. Zougmoré; J. M. B. Ndjaka (International Journal of Photoenergy)
This paper reports numerical investigation, using SCAPS-1D program, of the influence of Cu2ZnSnS4 (the so-called CZTS) material features such as thickness, holes, and defects densities on the performances of ZnO:Al/i-ZnO/CdS/CZTS/Mo solar cells structure. We found that the electrical parameters are seriously affected, when the absorber thickness is lower than 600 nm, mainly due to recombination at CZTS/Molybdenum interface that causes the short-circuit current density loss of 3.6 mA/cm2. An additional source of recombination, inside the absorber layer, affects the short-circuit current density and produces a loss of about 2.1 mA/cm2 above this range of absorber thickness. The J-V characteristic shows that the performance of the device is also limited by a double diode behavior. This effect is reduced when the absorber layer is skinny. Our investigations showed that, for solar cells having a CZTS absorber layer of thin thickness and high-quality materials (defects density ~1015 cm−3), doping less than 1016 cm−3 is especially beneficial. Such CZTS based solar cell devices could lead to conversion efficiencies higher than 15% and to improvement of about 100 mV on the open-circuit voltage value. Our results are in conformity with experimental reports existing in the literature.